Plasma Vitamin E and the Risk of First Stroke in Hypertensive Patients: A Nested Case-Control Study - Song, Yun; Li, Jingyi; Liu, Lishun; Xu, Richard; Zhou, Ziyi; Xu, Benjamin; Lin, Tengfei; Chen, Ping; Li, Huan; Li, Youbao; Liu, Chengzhang; Huang, Xiao; et al. (Frontiers in Nutrition, 2021)
Background: The association between plasma vitamin E levels and first stroke risk in men and women remains unclear. Objective: We aimed to examine the prospective association between plasma vitamin E and first stroke, and evaluate the effect modifiers for the association, among hypertensive patients. Design: The study sample was drawn from the China Stroke Primary Prevention Trial (CSPPT), which randomized a total of 20,702 hypertensive patients to a double-blind, daily treatment with either 10mg enalapril and 0.8mg folic acid or 10 mg enalapril alone. This nested case-control study, including 618 first stroke cases and 618 controls matched for age, sex, treatment group and study site, was conducted after the completion of the CSPPT. Results: The median follow-up duration was 4.5 years. Among men, a significantly higher risk of first stroke (adjusted OR, 1.67; 95%CI: 1.01, 2.77) was found for those with plasma vitamin E ≥7.1 μg/mL (≥quartile 1) compared with those with plasma vitamin E <7.1 μg/mL. Subgroup analyses further showed that the associaton between vitamin E (≥7.1 vs. <7.1 μg/mL) and first stroke in men was significantly stronger in non-drinkers (adjusted OR, 2.64; 95%CI: 1.41, 4.96), compared to current drinkers (adjusted OR, 0.84; 95% CI: 0.43, 1.66, P-interaction=0.008). However, there was no significant association between plasma vitamin E and first stroke in women (P-interaction between sex and plasma vitamin E =0.048). Conclusions: Among Chinese hypertensive patients, there was a significant positive association between baseline plasma vitamin E and the risk of first stroke in men, but not in women.